Comparison of Transforaminal Lumbar Interbody Fusion with Direct Lumbar Interbody Fusion: Clinical and Radiological Results - Lee, Young Seok (J Korean Neurosurg Soc, 2014)
OBJECTIVE: The use of direct lumbar interbody fusion (DLIF) has gradually increased; however, no studies have directly compared DLIF and transforaminal lumbar interbody fusion (TLIF). We compared DLIF and TLIF on the basis of clinical and radiological outcomes. METHODS: A retrospective review was performed on the medical records and radiographs of 98 and 81 patients who underwent TLIF and DLIF between January 2011 and December 2012. Clinical outcomes were compared with a visual analog scale (VAS) and the Oswestry disability index (ODI). The preoperative and postoperative disc heights, segmental sagittal/coronal angles, and lumbar lordosis were measured on radiographs. Fusion rates, operative time, estimated blood loss (EBL), length of hospital stay, and complications were assessed. RESULTS: DLIF was superior to TLIF regarding its ability to restore disc height, foraminal height, and coronal balance (p<0.001). As the extent of surgical level increased, DLIF displayed significant advantages over TLIF considering the operative time and EBL. However, fusion rates at 12 months post-operation were lower for DLIF (87.8%) than for TLIF (98.1%) (p=0.007). The changes of VAS and ODI between the TLIF and DLIF were not significantly different (p>0.05). CONCLUSION: Both DLIF and TLIF are less invasive and thus good surgical options for treating degenerative lumber diseases. DLIF has higher potential in increasing neural foramina and correcting coronal balance, and involves a shorter operative time and reduced EBL, in comparison with TLIF. However, DLIF displayed a lower fusion rate than TLIF, and caused complications related to the transpsoas approach.